THE TECHNIQUE OF APPLYING DIGITAL PRINTS TO EXPLORE THE QUALITY OF THE RETRACTION OF THE GINGIVAL MARGIN - E. N. ZHULEV; Y. A. VOKULOVA (Кубанский научный медицинский вестник, 2017)
The display of the boundaries prosthetic bed is impossible without pushing the gingival margin. Manufacturers of dental materials today offer a wide variety of means for retraction: of yarns of different design and size, pastes, gels. Most often for these purposes, a retraction filament impregnated with various drug compounds. One of the new methods of taking impression is a system of digital three-dimensional scanning, allowing to obtain optical impressions. To study and analyze the quality of the retraction of the gingival margin using a variety of tools and methods to assess the magnitude of the horizontal and vertical retractions, you should use the system intraoral laser scanning. This article presents a technique for applying digital prints to explore the quality of the retraction of the gingival margin.